Roll-to-plate fabrication of microfluidic devices with rheology-modified thiol-ene resins. (20th June 2016) - Senkbeil, Silja; Aho, Johanna; Yde, Leif; Lindvold, Lars R; Stensborg, Jan F; Rantanen, Jukka; Lafleur, Josiane P; Kutter, Jörg P
Abstract: In this paper, the replication possibilities of microfluidic channels by UV-roll-to-plate fabrication were investigated and a study of rheology-modified thiol-ene for the application in such a UV-roll-to-plate setup was conducted. The system allows the manufacture of channels with aspect ratios of 2:1 and a maximal channel depth of 90 μ m as well as the sealing of the finished devices with patterning and sealing speeds of up to 19 m min −1 . By adding fumed silica nanoparticles to the uncured resins, it was possible to alter the rheological behavior of the resin system to fabricate shallow microfluidic channels with 40 × 95 μ m cross-sectional dimensions. Moreover, deeper (90 μ m) channels can be fabricated with highly viscous resins based on thiol-terminated oligomers. As a demonstration, capillary electrophoresis chips were prepared and tested for a simple separation of two fluorescent dyes.